2019
DOI: 10.5194/acp-19-1901-2019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Asian monsoon strength and transport of surface aerosols to the Asian Tropopause Aerosol Layer (ATAL): interannual variability and decadal changes

Abstract: In this study, we have investigated the interannual variability and the decadal trend of carbon monoxide (CO), carbonaceous aerosols (CA) and mineral dust in the Asian Tropopause Aerosol Layer (ATAL) in relation to varying strengths of the South Asian summer monsoon (SASM) using MERRA-2 reanalysis data (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Results show that during this period, the aforementioned ATAL constituents exhibit strong interannual variability and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 67 publications
5
46
0
Order By: Relevance
“…Only limited information on the chemical composition of the ATAL particles is available from measurements so far. From simulations, there is evidence that desert dust is lifted to UTLS altitudes and entrained into the ATAL (Fadnavis et al, 2013;Lau et al, 2018;Yuan et al, 2019). Aircraft in situ measurements suggest that at lower altitudes the chemical composition of ATAL particles are dominated by carbonaceous and sulphate materials, consistent with the expectation that aerosol trends in the UTLS in the past decades are under increasing influence of sulphur emissions in Asia (Martinsson et al, 2014;Vernier et al, 2015;Fadnavis et al, 2019a).…”
supporting
confidence: 54%
“…Only limited information on the chemical composition of the ATAL particles is available from measurements so far. From simulations, there is evidence that desert dust is lifted to UTLS altitudes and entrained into the ATAL (Fadnavis et al, 2013;Lau et al, 2018;Yuan et al, 2019). Aircraft in situ measurements suggest that at lower altitudes the chemical composition of ATAL particles are dominated by carbonaceous and sulphate materials, consistent with the expectation that aerosol trends in the UTLS in the past decades are under increasing influence of sulphur emissions in Asia (Martinsson et al, 2014;Vernier et al, 2015;Fadnavis et al, 2019a).…”
supporting
confidence: 54%
“…Although our observations support the hypothesis of significant input into the anticyclone from a chimney region centred near the southern flank of the Tibetan Plateau, the campaign did not cover a wide enough region to characterize the relative contributions of convection from other sources based solely on the observations. Recent studies have demonstrated horizontal transport of convective outflow from locations over China into the ASM anticyclone (Lee et al, 2019;Yuan et al, 2019) as well as injections into the ASM anticyclone from tropical typhoons (Li et al, 2017;Li et al, 2020). Evidence for such import into the air masses probed in 2017 has been shown in trajectory studies (Bucci et al, 2019;Lee et al, 2020).…”
Section: Rapid Convective Transportmentioning
confidence: 95%
“…The increase of anthropogenic emissions over India may partially offset the overall decreasing trend in Asia and lead to smaller decreasing trends in India than in the rest of Asia. In addition, Yuan et al [63] reported that CO has increased in the Asian Tropopause Aerosol Layer, a planetary-scale aerosol layer situated 13-18 km above sea level partially covering the northern part of India. This amount of CO and its variation are detected by satellite instruments.…”
Section: Temporal-spatial Variations and Trends In Atmospheric Carbonmentioning
confidence: 99%